2013
DOI: 10.1007/s00256-013-1771-8
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of urate deposition within the extremities in gout: a review of 148 dual-energy CT cases

Abstract: In this observational study, we provide for the first time a detailed analysis of extremity urate distribution in gout, which both supports and augments to the current understanding based on clinical and microscopic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
50
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 22 publications
8
50
1
Order By: Relevance
“…Contrary to our hypothesis, our results indicate that the dorsiflexors of the ankle are not affected by strength deficits to the same extent as the plantarflexors of the ankle in people with gout. This finding may be related to the pattern of crystal deposition and patient symptoms reported in the foot and ankle, in which anterior ankle structures, including the tibialis anterior tendon are less frequently involved compared with the posterior ankle and Achilles tendon [6,8]. Our results are consistent with previous studies investigating the ankle in other chronic inflammatory arthritic conditions [27] in which neural…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to our hypothesis, our results indicate that the dorsiflexors of the ankle are not affected by strength deficits to the same extent as the plantarflexors of the ankle in people with gout. This finding may be related to the pattern of crystal deposition and patient symptoms reported in the foot and ankle, in which anterior ankle structures, including the tibialis anterior tendon are less frequently involved compared with the posterior ankle and Achilles tendon [6,8]. Our results are consistent with previous studies investigating the ankle in other chronic inflammatory arthritic conditions [27] in which neural…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has observed tophaceous deposition in the Achilles, peroneal and the tibialis posterior muscle tendons in people with gout [6,8]. Tendons have important functional roles, both in generating and absorbing mechanical work during ambulation [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DECT provided important insights, particularly into the pathology of gout. The distribution of urate deposits within the extremities of patients with suspected gout was evaluated in an observational study, which found urate deposition in foot (56.1%), in knee (53.4%), in ankle (27.7%), in elbow (16.9%), and in hand and wrist (16.9%), respectively (45).…”
Section: Imaging Techniques In Goutmentioning
confidence: 99%
“…The common sites involved in knee are the popliteus tendon, cruciate ligaments, and quadriceps tendon. 2 Although patellar tendon has been mentioned as a possible involvement site, to our knowledge, only three case reports exist in the literature, two of which were reported in triathletes mimicking patellar tendonitis precipitated due to prolonged exercises. [3][4][5] In this article, we report a 34-year-old male patient with eight years history of gout who presented with one week history of pain and swelling of extremities.…”
mentioning
confidence: 99%